1981
DOI: 10.1002/art.1780240310
|View full text |Cite
|
Sign up to set email alerts
|

Production of agglutinators and rheumatoid factors in plasma cells of rheumatoid and nonrheumatoid synovial tissues

Abstract: Immunohistochemical studies were performed in synovial tissues from 40 patients with rheumatoid arthritis (RA), 9 with juvenile rheumatoid arthritis (JRA), 7 with psoriatic arthritis, and 4 with various rheumatic diseases. Overall synthesis of IgG– and/or IgM–rheumatoid factor (RF) was found in all patients with seropositive RA and JRA, in 75% of patients with seronegative RA, and in 1 patient with psoriatic arthritis. Agglutinator producing cells were found in 77% of the samples from seropositive RA and in 44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…In the 8 cultures in which IgG-RF was detectable, it represented a mean of 2.6% of the total synthesized IgG. Thus, our data are not in agreement with the results of immunofluorescence studies of synovium (1,6,24), in which IgG-RF was detected by staining in 20-60% of IgG-producing plasma cells. It is unlikely that our assay underestimated the amount of IgG-RF, since the method was standardized against a preparation of polyclonal IgG-RF that had been rigorously purified from the serum of a patient with RA (12).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In the 8 cultures in which IgG-RF was detectable, it represented a mean of 2.6% of the total synthesized IgG. Thus, our data are not in agreement with the results of immunofluorescence studies of synovium (1,6,24), in which IgG-RF was detected by staining in 20-60% of IgG-producing plasma cells. It is unlikely that our assay underestimated the amount of IgG-RF, since the method was standardized against a preparation of polyclonal IgG-RF that had been rigorously purified from the serum of a patient with RA (12).…”
Section: Discussioncontrasting
confidence: 97%
“…They concluded that there is extensive synthesis of self-associating IgG-RF in seropositive and seronegative rheumatoid synovial tissue. Recently, Fehr et a1 (24), using an indirect method of C3 binding and immunofluorescence, reported that 95% of seropositive and 72% of seronegative rheumatoid synovial tissues contained IgG-RF-producing cells, and that RF was produced by 60% of IgG-synthesizing cells and by 51-72% of IgM-producing cells. From these reports, it is evident that existing data are highly variable regarding the quantitation of the synthesis and secretion of IgM-RF and IgG-RF in rheumatoid synovium.…”
Section: Discussionmentioning
confidence: 99%
“…RF is also produced and concentrated in the rheumatoid synovial tissue (23)(24)(25)(26)(27)(28). IgG1, the dominant ACPA isotype, is recognized by all of the so far described RA-derived RF (29).…”
mentioning
confidence: 99%
“…Limited proteolysis of IgGs creates new antigenic sites (Fehr, 1971). Antibodies to the neoepitopes created by limited cleavage of human IgG by a variety of proteinases are found in human serum and these can be elevated in some auto-immune disorders, including arthritis (Fehr, 1971(Fehr, , 1981. Whether these will react with cleavage neoantigens on murine Igs, and what effect such reaction might have on the development of the immune response to parenteral use of a murine monoclonal antibody is unknown.…”
Section: Discussionmentioning
confidence: 99%